Key Developmental Opportunities for Long-term Organization Development of G Commercial Bank China : A Mixed Method Research - Wu, YuJie; Preudhikulpradab, Sirichai (ABAC ODI JOURNAL Vision. Action. Outcome, 2021)
This research-based article employs needs assessment research. The research site is at G Commercial Bank in China. The study comprises two objectives: 1) to examine the current and expected situations of the five performance-related factors, consisting of training & development, work-life balance, supervision, organizational commitment, and perceived AI utilization, and 2) to propose an OD intervention for improvement of the aforementioned performance-related factors. This study employs a semi-structured questionnaire containing fixed choices and open-ended questions for data collection from the respondents. The data analysis and synthesis procedures include descriptive statistics, PNIModified, and contents analysis. The actual sample is 138 respondents who completed the questionnaire, and 35 out of 138 respondents provide the qualitative suggestions in the open-ended question section. The key findings based on the quantitative and qualitative data revealed that the priority needs for Organization Development Interventions for improvement comprise work-life balance as the 1st priority need, perceived AI utilization as the 2nd priority needs, training & development as the 3rd priority need, the supervision as the 4th priority, and organizational commitment as the 5th priority. A set of OD interventions for improvements proposed, where the work-life balance, perceived AI utilization, training &development, and supervision were regarded as the interdependent factors for the total improvement program of their employees’ performance. At the same time, the current organization continuously nurtured the current condition of organizational commitment.